Collaboration Between Madrasahs and The Business Sector In Developing an Islamic Edupreneurship Ecosystem - Megawati, Megawati; Anwar, Kaspul; Kompri, Kompri; Mastikawati, Mastikawati (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2024)
This study examines the forms, mechanisms, and outcomes of collaboration between MAN 2 Kota Jambi and industry partners in developing an Islamic edupreneurship ecosystem. Using a qualitative case study design, the research explores partnership practices involving program planning, implementation, and evaluation. Data were collected through in-depth interviews, field observations, and document analysis, then analyzed using thematic procedures. The findings indicate that strategic partnerships with universities, government agencies, and business sectors significantly enhance students’ technical competencies through laboratory practice, fisheries training, language development, and vocational skill programs. These collaborations also foster students’ creativity, confidence, and Islamic work ethics—reflected in discipline, honesty, and responsibility during training activities. Shared motivations between the madrasah and industry—such as improving learning quality, addressing facility limitations, and fulfilling CSR commitments—create mutually beneficial relationships that strengthen the institutional reputation of MAN 2 Kota Jambi as an innovative Islamic school. Despite notable achievements, challenges remain, including sustaining partner commitment and harmonizing activity schedules. Overall, the study proposes a conceptual model of an Islamic edupreneurship ecosystem that integrates experiential learning, partnership governance, and sharia-based values as the foundation for ethical entrepreneurial development in madrasah education.